Empirical analysis on the impact of asean free trade area (afta) on trade flows and patterns among member countries. - Tan, Sylvia Mui Sze. (2008)
The objective of this paper is to investigate the impact of Asean Free Trade Agreement (AFTA) on intra-ASEAN trade flows and patterns across twenty-one sectors for four countries - Malaysia, Thailand, Indonesia and Philippines.